Non-Archimedean stability of the monomial functional equations - Mirmostafaee,A. K. (Tamsui Oxford Journal of Mathematical Sciences)
We study the stability of the functional equation △(superscript n subscript x)f(y)=n!f(x) innon-Archimedean spaces in the spirit of Hyers-Ulam-Rassias-Gǎvruţa. We will give an example to show that some results in the stability of monomial equations in real normed spaces are not valid in non-Archimedean normed spaces.